A Pola Kelembagaan Sosial Ekonomi Punggawa Dan Pedagang Ikan Di Pangkalan Pendaratan Ikan (PPI) Selili Kota Samarinda.: Pola Kelembagaan Sosial Ekonomi Punggawa Dan Pedagang Ikan Di Pangkalan Pendaratan Ikan (PPI) Selili Kota Samarinda. - Ikhwan Fadhli; Bambang Indratno Gunawan; Fitriyana (2339-1324, 2024)
Ikhwan Fadhli, 2022. Socio-Economic Institutional Patterns of Retainers and Fish Traders at the Selili Fish Landing Base (PPI) Samarinda City. (Supervised by Dr. H. Bambang Indratno Gunawan, S.Pi, M.Si. and Mrs. Dr. Hj. Fitriyana, S.Pi, M.Si.). The purpose of this study was to determine the institutional pattern of Punggawa and Fish Traders at PPI. Selili. Knowing the formulation of development strategies based on SWOT analysis, by identifying internal and external factors, IFAS and EFAS, strategy diagrams, and alternative strategies. This research was conducted from October 2021 to September 2022. Types of research research data using descriptive quantitative data and primary data obtained by interviews using questionnaire. The result of this research is the pattern of Punggawa and Fish Traders at the Fish Landing Base (PPI) Selili, which are agents and retailers as a component of fish marketing distribution, all of which are distributed through a trading system. The distribution channel for fish marketing begins with Punggawa who buys fish from collectors and is marketed within the PPI., then Fish Traders who buy fish from Punggawa and re-market outside the PPI. The formulation of the development strategy based on SWOT analysis, obtained the results of a strength value of 0.557 and an opportunity value of 0.701. then occupy the position of quadrant I carrying the strategy (S-O) which is aggressive by maximizing strengths and opportunities. Keywords: Institutional Patterns, Socio-Economic, Retainers, Fish Traders, Development Strategies, SWOT Factors.